A Study on Job Satisfaction of Primary School Teachers in Relation to their Educational Qualifications, Occupations and Mental Health Stress (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Teacher burnout, depression, and other mental health issues are investigated as potentialcauses of low work satisfaction among elementary school educators. The study collects informationfrom a wide range of primary school educators via a combination of survey and interview techniques.According to the results, there is a strong correlation between educational attainment and worksatisfaction. Workload and administrative support are only two examples of the occupational aspects theresearch identified as having an effect on job satisfaction. Furthermore, it emphasizes the need forassistance and interventions to improve teacher well-being by highlighting the impact of mental healthstress on work satisfaction. These findings may be used to shape policies and practices in elementaryeducation that benefit teachers' mental health and happiness on the job. The current study will recruit440 primary school teachers from the Hyderabad region, including both male and female instructorsfrom private and public schools in both rural and urban areas. A basic random sampling approach willbe used to choose a sample of this size. Here are some example frequencies